(untitled) (World Bulletin of Management and Law, 2022)
Brand image and advertising are an important part of any company’s performance as brand image is an implicit tool that has the potential to positively influence consumers’ buying behavior and advertising is a motivating factor for any type of business as it is the Mediation is the message you send that stays in the client’s mind. The purpose of the study was to examine the impact of brand image and advertising on the purchasing behavior of Iraqi consumers. The data collection technique used was a questionnaire survey with a non-probabilistic convenient sampling technique. There were 200 questionnaires have been distributed, and 175 replies were collected over 1 month. The findings suggest that brand image and advertising have a considerable favorable impact on customers’ purchasing decisions. People have favorable impressions of a company’s image. Iraqi youth are more aware of their social status, which is why they choose branded products, and advertising has a beneficial impact on their purchasing behavior, according to research. Finally, the paper discusses the study’s shortcomings, consequences, and recommendations for further research